INFLUÊNCIA DAS VARIAÇÕES DO NÍVEL FREÁTICO NA QUÍMICA DA ÁGUA SUBTERRÂNEA, AQÜÍFERO PIRANEMA – BACIA DE SEPETIBA, RJ - Marques, Eduardo D.; Tubbs, Décio; Silva-Filho, Emmanoel V. (Geochimica Brasiliensis, 2012)